2016
DOI: 10.1177/2158244016633731
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation on Mobile Banking Service Adoption in Rural Karnataka

Abstract: Government of India (GOI) initialized financial inclusion campaign to quell exclusion. The campaign did not gain expected progress. Government employed technologies to speed up the process. Among banking technologies, mobile banking appeared as a possible solution for financial exclusion with wide mobile phone coverage. Inputs on rural people's intention toward technologies for effective financial inclusion were essential. Technology adoption factors, performance expectancy, effort expectancy, social influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 197 publications
(293 reference statements)
5
47
1
2
Order By: Relevance
“…The high explanatory power of performance expectancy gives rise to the first finding: performance expectancy is the determinant variable in the acceptance of cryptocurrency financial technologies. This finding is consistent with other studies that have found this variable to be determinant in the intention to use a given financial technology, including a biometric payment service (Kim et al, 2018), plastic money (Makanyeza and Mutambayashata, 2018), online banking (Khan et al, 2017; Sánchez-Torres et al, 2018), and m-banking (Kishore and Sequeira, 2016; Nisha, 2016; Farah et al, 2018; Hussain et al, 2018; Warsame and Ireri, 2018). Studies about cryptocurrencies and bitcoin in particular have reached the same results regarding the influence of performance expectancy on the intention to use, including in relation to electronic payments with cryptocurrencies (Mendoza-Tello et al, 2018) and bitcoin acceptance in China (Shahzad et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The high explanatory power of performance expectancy gives rise to the first finding: performance expectancy is the determinant variable in the acceptance of cryptocurrency financial technologies. This finding is consistent with other studies that have found this variable to be determinant in the intention to use a given financial technology, including a biometric payment service (Kim et al, 2018), plastic money (Makanyeza and Mutambayashata, 2018), online banking (Khan et al, 2017; Sánchez-Torres et al, 2018), and m-banking (Kishore and Sequeira, 2016; Nisha, 2016; Farah et al, 2018; Hussain et al, 2018; Warsame and Ireri, 2018). Studies about cryptocurrencies and bitcoin in particular have reached the same results regarding the influence of performance expectancy on the intention to use, including in relation to electronic payments with cryptocurrencies (Mendoza-Tello et al, 2018) and bitcoin acceptance in China (Shahzad et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reached the same conclusion: this variable does not influence the adoption of other financial technologies, such as plastic money (Makanyeza and Mutambayashata, 2018) and online banking (Khan et al, 2017). However, opposite findings have also been reported, as in the m-banking studies by Kishore and Sequeira (2016); Mahfuz et al (2016), and Warsame and Ireri (2018) that have found social influence to be relevant to adoption. The results of cryptocurrency acceptance studies are similarly contradictory.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Some evidences in this way are [43] for the use of a payment authentication system based on biometrics; [44] in the behavioral intention to adopt plastic money; [45] on the use of financial websites; [46] for adopting online banking. In the use of mbanking [26,[47][48][49][50][51] obtain similar results. Regarding specific literature on cryptos results in [7][8][9][10][11][12]14,15,18,20,21] also suggests that PE is the key factor to explain intention to use, so the following hypothesis can be stated: Hypothesis 1 (H1).…”
Section: A Model To Explain the Acceptance Of Cryptocurrencies By Houmentioning
confidence: 58%
“…The banking industry begins to adapt to technology since 1960, and they are still experiencing the changes in technologies in the management of banking information from time to time [1,2]. Traditionally, a large number of banking services can obtain from the bank branches located near customers.…”
Section: Introductionmentioning
confidence: 99%